Whole-exome sequencing in 168 Korean patients with inherited retinal degeneration - Dae Joong Ma; Hyun-Seob Lee; Kwangsoo Kim; Seongmin Choi; Insoon Jang; Seo-Ho Cho; Chang Ki Yoon; Eun Kyoung Lee; Hyeong Gon Yu (BMC, 2021)
Abstract Background To date, no genetic analysis of inherited retinal disease (IRD) using whole-exome sequencing (WES) has been conducted in a large-scale Korean cohort. The aim of this study was to characterise the genetic profile of IRD patients in Korea using WES. Methods We performed comprehensive molecular testing in 168 unrelated Korean IRD patients using WES. The potential pathogenicity of candidate variants was assessed using the American College of Medical Genetics and Genomics and the Association for Molecular Pathology variant interpretation guidelines, in silico prediction tools, published literature, and compatibility with known phenotypes or inheritance patterns. Results Causative variants were detected in 86/168 (51.2%) IRD patients, including 58/107 (54.2%) with retinitis pigmentosa, 7/15 (46.7%) with cone and cone-rod dystrophy, 2/3 (66.6%) with Usher syndrome, 1/2 (50.0%) with congenital stationary night blindness, 2/2 (100.0%) with Leber congenital amaurosis, 1/1 (100.0%) with Bietti crystalline dystrophy, 1/1 (100.0%) with Joubert syndrome, 9/10 (90.0%) with Stargardt macular dystrophy, 1/10 (10.0%) with vitelliform macular dystrophy, 1/11 (9.1%) with other forms of macular dystrophy, and 3/4 (75.0%) with choroideraemia. USH2A, ABCA4, and EYS were the most common causative genes associated with IRD. For retinitis pigmentosa, variants of USH2A and EYS were the most common causative gene mutations. Conclusions This study demonstrated the distribution of causative genetic mutations in Korean IRD patients. The data will serve as a reference for future genetic screening and development of treatment modalities for Korean IRD patients.